Whiffet Squirrel - Greene, Julia (Salt Lake City, UT : Project Gutenberg, 2007)
"Whiffet Squirrel" by Julia Greene is a children's story written in the early 20th century. This charming tale revolves around the whimsical adventures of three little red squirrels$1 (BWhiffet, Skiffet, and Skud$1 (Bwho move into a birdhouse, believing it to be their new home. The story explores themes of childhood mischief, curiosity, and the joy of exploration, making it a delightful read for young audiences. The narrative follows the little Squirrel family as they settle into their new abode in an old chestnut tree, where they enjoy life and embark on various escapades. Whiffet, the smallest and most adventurous, leads her brothers into a daring quest to steal a doll's trunk and its contents from a sleeping girl named Polly. They successfully take several of her doll's clothes and vanity items, which bring them joy and excitement. However, their actions catch up with them when Polly discovers her treasures are missing. The story culminates with a playful twist, highlighting the innocence of childhood and the unintended consequences of their mischief as they navigate their new life. (This is an automatically generated summary.)s
Release date is 2007-11-17
E-text prepared by Roger Frank and the Project Gutenberg Online Distributed Proofreading Team (https://www.pgdp.net)
Keywords: Squirrels -- Juvenile fiction